Impact of war on foreign students' satisfaction with quality of dental and medical education in Ukraine - Myroslav GONCHARUK-KHOMYN; Vasyl KALIY; Renata POHORILYAK; Alessandro CAVALCANTI; Andrii KENIUK; Yasemin YAVUZ; Boychuk OLENA (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The objective of this study was to evaluate the changes in foreign students' satisfaction with the quality of dental and medical education considering the impact of the war in Ukraine. The present study was organized in the form of a questionnaire-based survey among 300 foreign students of Medical Faculty and Faculty of Dentistry in Ukraine. The questionnaire was ad mistered via Google form in a multiple-choice, closed-ended format. Students' satisfaction with environment safety and comfort (p < 0.05) and with the collaborative learning offered (p < 0.05) statistically decreased during the war. Sixty percent of the variability in the mean of students' satisfaction with the quality of education during the war could be explained by the satisfaction rate before the war. The need of migration from Ukraine had a stronger inverse correlation with education quality (r = -0.58) than the fact of the war itself (r = -0.32). The war in Ukraine has had a negative impact on the educational process of foreign medical and dental students, even though the quality of education was considered by students to be as high as before and during the war. The personal effort of professors, the quality of study materials, and adequate technical support could potentially overcome the negative impact of the war on student satisfaction with the quality of medical and dental education by the online mode, if the academic medium could be protected from the direct impact of the war or if the influence of the war within the university community could be minimized.